Coupling of D2R Short but not D2R Long receptor isoform to the Rho/ROCK signaling pathway renders striatal neurons vulnerable to mutant huntingtin. (24th October 2016) - Galan‐Rodriguez, Beatriz; Martin, Elodie; Brouillet, Emmanuel; Déglon, Nicole; Betuing, Sandrine; Caboche, Jocelyne
Abstract: Huntington's disease, an inherited neurodegenerative disorder, results from abnormal polyglutamine extension in the N‐terminal region of the huntingtin protein. This mutation causes preferential degeneration of striatal projection neurons. We previously demonstrated, in vitro, that dopaminergic D2 receptor stimulation acted in synergy with expanded huntingtin to increase aggregates formation and striatal death through activation of the Rho/ROCK signaling pathway. In vivo, in a lentiviral‐mediated model of expanded huntingtin expression in the rat striatum, we found that the D2 antagonist haloperidol protects striatal neurons against expanded huntingtin‐mediated toxicity. Two variant transcripts are generated by alternative splicing of the of D2 receptor gene, the D2R‐Long and the D2R‐Short, which are thought to play different functional roles. We show herein that overexpression of D2R‐Short, but not D2R‐Long in cell lines is associated with activation of the RhoA/ROCK signaling pathway. In striatal neurons in culture, the selective D2 agonist Quinpirole triggers phosphorylation of cofilin, a downstream effector of ROCK, which is abrogated by siRNAs that knockdown both D2R‐Long and D2R‐Short, but not by siRNAs targeting D2R‐Long alone. Aggregate formation and neuronal death induced by expanded huntingtin, were potentiated by Quinpirole. This D2 agonist‐mediated effect was selectively inhibited by the siRNA targeting both D2R‐Long and D2R‐Short but not D2R‐Long alone. Our data provide evidence for a specific coupling of D2R‐Short to the RhoA/ROCK/cofilin pathway, and its involvement in striatal vulnerability to expanded huntingtin. A new route for targeting Rho‐ROCK signaling in Huntington's disease is unraveled with our findings. Abstract : Specific coupling of D2R Short to Rho/Rock signaling and striatal vulnerability in Huntington's Disease.